Effectiveness of the baby‐friendly community initiative on exclusive breastfeeding in Kenya. Issue 3 (2nd February 2021) - Kimani‐Murage, Elizabeth W.; Kimiywe, Judith; Mutoro, Antonina N.; Wilunda, Calistus; Wekesah, Frederick Murunga; Muriuki, Peter; Mwangi, Bonaventure M.; Samburu, Betty Mogesi; Madise, Nyovani Janet; McGarvey, Stephen T.; Griffiths, Paula L.
Abstract: The baby‐friendly hospital initiative (BFHI) promotes exclusive breastfeeding (EBF) in hospitals, but this is not accessible in rural settings where mothers give birth at home, hence the need for a community intervention. We tested the effectiveness of the baby‐friendly community initiative (BFCI) on EBF in rural Kenya. This cluster randomized study was conducted in 13 community units in Koibatek sub‐county. Pregnant women aged 15–49 years were recruited and followed up until their children were 6 months old. Mothers in the intervention group received standard maternal, infant and young child nutrition counselling, support from trained community health volunteers, health professionals and community and mother support groups, whereas those in the control group received standard counselling only. Data on breastfeeding practices were collected longitudinally. The probability of EBF up to 6 months of age and the restricted mean survival time difference were estimated. A total of 823 (intervention group n = 351) pregnant women were recruited. Compared with children in the control group, children in the intervention group were more likely to exclusively breastfeed for 6 months (79.2% vs. 54.5%; P < .05). Children in the intervention group were also exclusively breastfed for a longer time, mean difference (95% confidence interval [CI]) 0.62 months (0.38, 0.85; P < .001). The BFCI implemented within the existing health system and including community and mother support groups led to a significant increase in EBF in a rural Kenyan setting. This intervention has the potential to improve EBF rates in similar settings.